Melt-processed PLA/HA platelet nanoparticle composites produced using tailored dispersants - Parsons, Andrew J.; Walton, Kirsty; Hild, Frederic; Ilchev, Alex; Gimeno-Fabra, Miquel; Tomczynska, Magdelena M.; Ward, Michael; Canciani, Alessia; Choong, Gabriel Y.H.; De Focatiis, Davide S.A.; Lester, Edward; Grant, David M.; et al. (2016)
Hydroxyapatite (HA) nanoparticles, similar to those seen in the structure of human bone, have been produced via hydrothermal synthesisand used to produce nanocomposite materials via melt blending with poly(lactic acid)(PLA). Both of these processes are scalable and commercially relevant. Tailored dispersants were developed and used to improve the dispersion of the HA. Modest improvements in flexural properties were observed (max increases 30% of dry modulus, 13% of wet strength). Rheometry is not suggestive of achieving percolation,so there is potential to improve mechanical properties further. It was established that very dry processing conditions are essential to maintaining the molecular weight of the PLA during processing and that the use of the tailored dispersants can also help to mitigateprocess-induced degradation.MicroCT has proved to be a useful quality control tool to support TEM analysis.